1954
DOI: 10.1037/h0054967
|View full text |Cite
|
Sign up to set email alerts
|

S-R compatibility: Correspondence among paired elements within stimulus and response codes.

Abstract: The present paper is the second dealing with the usefulness of the concept of S-R compatibility for behavior theory. This concept concerns the effects of a class of variables that influence task difficulty in experiments in which learning, complexity (amount of information), and discriminability are controlled. Compatibility effects are conceived as resulting from hypothetical information transformation processes (encoding and/or decoding) that intervene between receptor and effector activity. The rate of proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(173 citation statements)
references
References 13 publications
9
162
2
Order By: Relevance
“…The SRC effect, too, is often credited in part to activation of the corresponding response via the direct route, as in Kornblum et al's model, but also to differences in time for response activation to occur by way of the short-term location associations of the indirect route. Indeed, some authors (e.g., Fitts & Deininger, 1954) have attributed the SRC effect entirely to "S-R translations" of the indirect route.…”
Section: Dual-route Modelsmentioning
confidence: 99%
“…The SRC effect, too, is often credited in part to activation of the corresponding response via the direct route, as in Kornblum et al's model, but also to differences in time for response activation to occur by way of the short-term location associations of the indirect route. Indeed, some authors (e.g., Fitts & Deininger, 1954) have attributed the SRC effect entirely to "S-R translations" of the indirect route.…”
Section: Dual-route Modelsmentioning
confidence: 99%
“…Fitts and Seeger (1953), Fitts and Deininger (1954), and Morin and Grant (1955) demonstrated S-R compatibility with visual stimuli, Broadbent andGregory (1965) with tac.,tical stimulation, andSimoti, Hinrichs, andCraft (1970) with auditory stimuli. Ogden, Anderson, andRieck (1979) demonstrated that a strong S-R compatibility effect was shown in a dual task setting.…”
Section: Sandry and Wickensmentioning
confidence: 99%
“…In a series of early investigations, Fitts a-nhf---coll' ii e(agues T.e., Fitts & Seeger, 1953;Fitts & Deininger, 1954) demonstrated that choice-reaction time performance is not solely determined by the stimulus set nor response set, but is instead a function of specific stimulus and response pairings into S-R ensembles.…”
Section: Sandry and Wickensmentioning
confidence: 99%
“…This RT difference is called a stimulus-response (S-R) compatibility (SRC) effect (Fitts & Deininger, 1954; for a review see Proctor & Vu, 2006). In most theoretical accounts, the SRC effect is attributed at least in part to activation of the spatially corresponding response that occurs as a consequence of the similarity, or overlap, of the stimulus and response dimensions (De Jong, Liang, & Lauber, 1994;Kornblum, Hasbroucq, & Osman, 1990).…”
Section: Introductionmentioning
confidence: 99%